UJI VALIDITAS BAHAN AJAR BERBASIS DEEP LEARNING BERBANTUAN HEYZINE FLIPBOOK MATERI KERAGAMAN BUDAYA INDONESIA KELAS IV - Khatimah, Husnul; Chan, Faizal; Khoirunnisa, Khoirunnisa (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
Digital transformation in education demands flexible, interactive learning focused on developing 21st-century competencies. However, preliminary research conducted in fourth-grade students at SD 182/I Hutan Lindung (Protected Forest Elementary School) showed that the current teaching materials are still general, teacher-centered, and not tailored to the needs and characteristics of students. The materials have not optimally integrated deep learning, and the use of digital technology is still limited, resulting in one-way learning and minimal student participation. This results in the delivery of Indonesian Cultural Diversity material being textual, lacking contextual and visual elements. This results in low student enthusiasm, focus, and activeness in asking questions and discussing, and a lack of in-depth understanding of the material. These conditions cause the learning process to be one-way and not contextual and visual. As a result, students are less enthusiastic, active, and understand the subject matter. This study aims to test the validity of deep learning-based teaching materials assisted by flipbook heyzine on Indonesian Cultural Diversity material for fourth-grade elementary school students. This study uses a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The validation process was carried out by material experts, linguists, and design experts using a validation sheet as a research instrument. The data obtained were analyzed using quantitative and qualitative analysis techniques. The results showed that the validation of material experts obtained an average value of 4.90, validation of linguists was 4.88, and validation of design experts was 4.89, all of which were in the very valid category. Thus, the deep learning-based teaching material assisted by heyzine flipbooks was declared very valid and suitable for use in learning the material of Indonesian Cultural Diversity in grade IV of elementary school and can be continued to the implementation stage to test its practicality and impact on learning outcomes. ABSTRAKTransformasi digital dalam dunia pendidikan menuntut pembelajaran yang fleksibel, interaktif, dan berfokus pada pengembangan kompetensi abad ke-21. Namun, penelitian awal yang dilakukan di kelas IV SD 182/I Hutan Lindung, menunjukkan bahwa, bahan ajar yang digunakan saat ini masih bersifat umum, teacher-centered, dan belum disesuaikan dengan kebutuhan serta karakteristik peserta didik. Materi belum mengintegrasikan deep learning secara optimal dan pemanfaatan teknologi digital masih terbatas, sehingga pembelajaran cenderung satu arah dan minim partisipasi siswa. Hal ini menyebabkan penyampaian materi Keragaman Budaya Indonesia masih tekstual, kurang kontekstual dan visual, sehingga antusiasme, fokus, dan keaktifan siswa dalam bertanya maupun berdiskusi rendah, serta pemahaman terhadap materi belum berkembang secara mendalam. Kondisi tersebut menyebabkan proses pembelajaran menjadi satu arah dan tidak kontekstual dan visual. Akibatnya, peserta didik kurang antusias, aktif, dan memahami materi pelajaran. Penelitian ini bertujuan untuk menguji validitas bahan ajar berbasis deep learning berbantuan heyzine flipbook pada materi Keragaman Budaya Indonesia untuk peserta didik kelas IV sekolah dasar. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Proses validasi dilakukan oleh ahli materi, ahli bahasa, dan ahli desain dengan menggunakan lembar validasi sebagai instrumen penelitian. Data yang didapat dianalisis menggunakan teknik analisis kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa validasi ahli materi memperoleh nilai rata-rata sebesar 4,90, validasi ahli bahasa sebesar 4,88, dan validasi ahli desain sebesar 4,89, yang seluruhnya berada pada kategori sangat valid. Dengan demikian, bahan ajar berbasis deep learning berbantuan heyzine flipbook dinyatakan sangat valid dan layak digunakan dalam pembelajaran materi Keragaman Budaya Indonesia di kelas IV sekolah dasar dan dapat dilanjutkan pada tahap implementasi untuk menguji kepraktisan serta dampaknya terhadap capaian belajar.